To factor out completely, we should have reached the most simplified form,
first we should take out 2.
2(x2 - 3x - 18)
then we should factor out the inside of the parenthesis,
2(x - 6)(x + 3)
And that's the most simplified and factored out form.
The final answer is then the second option, <span>2(x − 6)(x + 3)</span>
Our x equals 0 so the answer is 0
Answer:
![n=\frac{1}{3}p+\frac{5}{6}](https://tex.z-dn.net/?f=n%3D%5Cfrac%7B1%7D%7B3%7Dp%2B%5Cfrac%7B5%7D%7B6%7D)
Step-by-step explanation:
In this question, you are solving for n.
Solve:
−2p + 6n = 5
We have to get "n" by itself, so add 2p to both sides.
6n = 2p + 5
Since the variable "n" has a number next to it, we have to get rid of that number in order to get our answer.
To do so, we would divide both sides by 6.
![n=\frac{2}{6}p+\frac{5}{6}](https://tex.z-dn.net/?f=n%3D%5Cfrac%7B2%7D%7B6%7Dp%2B%5Cfrac%7B5%7D%7B6%7D)
Simplify the equation further.
![n=\frac{1}{3}p+\frac{5}{6}](https://tex.z-dn.net/?f=n%3D%5Cfrac%7B1%7D%7B3%7Dp%2B%5Cfrac%7B5%7D%7B6%7D)
In order for the sales team to give the impression to their company that there was a large increasse in sales over a six month time period, they need to create a graph that have time period as the label of their x-axis or the horizontal label and sales as the label of their y-axis or the vertical label.
Answer:
EG = 13
Step-by-step explanation:
EG = EF + FG
EG = 4+ 9 = 13